2007
DOI: 10.1002/prot.21479
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of docking programs for predicting binding of Golgi α‐mannosidase II inhibitors: A comparison with crystallography

Abstract: Golgi alpha-mannosidase II (GMII), a zinc-dependent glycosyl hydrolase, is a promising target for drug development in anti-tumor therapies. Using X-ray crystallography, we have determined the structure of Drosophila melanogaster GMII (dGMII) complexed with three different inhibitors exhibiting IC50's ranging from 80 to 1000 microM. These structures, along with those of seven other available dGMII/inhibitor complexes, were then used as a basis for the evaluation of seven docking programs (GOLD, Glide, FlexX, Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 65 publications
3
50
0
Order By: Relevance
“…The commercial package GLIDE slightly outperformed the other academic available docking engines in terms of RMSD from experimental structures but the best result did not always correspond to the lowest energy conformation. This conclusion is in agreement with recent evaluation study for docking carbohydrate derivative to Zn-containing enzyme [37]. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 One calcium β-sandwich bacterial lectin…”
Section: Discussionsupporting
confidence: 81%
“…The commercial package GLIDE slightly outperformed the other academic available docking engines in terms of RMSD from experimental structures but the best result did not always correspond to the lowest energy conformation. This conclusion is in agreement with recent evaluation study for docking carbohydrate derivative to Zn-containing enzyme [37]. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 One calcium β-sandwich bacterial lectin…”
Section: Discussionsupporting
confidence: 81%
“…8 In 2007, the first version of FITTED was tested for its ability to dock mannosidase inhibitors which revealed the intricacies of modeling zinc coordination. 4 Later on, we also demonstrated that scoring metalloenzyme inhibitors was poor. 9 Throughout the years, docking programs have been assessed for their ability to dock inhibitors coordinating metal ions (often zinc) of metalloenzymes: AutoDock, DOCK, GOLD, and FlexX being widely used.…”
Section: ■ Introductionmentioning
confidence: 92%
“…Docking was carried out using the Glide v4.5 package of Schrodinger suite 2007. 37 Recent review of docking programs showed 47 that Glide belongs amongst the most accurate docking programs.…”
Section: Preparation Of Protein and Ligand Structures For Dockingmentioning
confidence: 99%